Pengolahan Sampah Plastik Jenis PP, PET dan PE Menjadi Bahan Bakar Minyak dan Karakteristiknya - Untoro Budi Surono; Ismanto Ismanto (Universitas Janabadra, 2016)
Increasing use of plastics is a consequence of the development of technology, industry and population. On one side, plastic invention has a tremendous positive impact, because the plastic has more advantages than other materials. But on the other hand, plastics have a harmful negative impact, so it is necessary to find the solution. Alternative handling of plastic waste is converting plastic waste into fuel oil. Processing plastic waste into fuel oil can be done with the process of cracking. In this study will be designed and tested a device to process plastic waste into fuel. In this study will try to process plastics waste of PE, PP and PET by thermal cracking. The main objective of this study was to determine the best operating conditions of device designed to obtain the results of the optimal fuel. From this study it can be concluded that PP produce the most oil with LPG needs of the least and the fastest processing time. At this experiment, PET does not produce oil but produces material in powder form. Oil from PP has higher calorific value than the calorific value of diesel, petrol, LPG and kerosene. Too high the rate of heat is causes the oil produced is reduced, while the smaller the rate of heat causes the processing time becomes longer. The resulting oil from processing of PP and PE based on the content of the number of carbon atoms approaching gasoline and kerosene.